Woke gaming : digital challenges to social injustice - Gray, Kishonna L.; Leonard, David J. (David Jason), 1973- (University of Washington Press, 2018)
"From #Gamergate to the 2016 election, to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of Warcraft and Tomb Raider, Woke Gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends."--